ATOMIC ABSORPTION SPECTROMETRIC METHOD FOR ESTIMATION OF DICLOFENAC SODIUM AND MEFENAMIC ACID IN PHARMACEUTICAL FORMULATIONS (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Diclofenac sodium and Mefenamic acid have been quantified in tablet dosage form by atomic absorption spectrometry (AAS). These methods are based on formation of the metal complexes of Diclofenac sodium and Mefenamic acid with cupric chloride and cobaltous chloride. The first method is based on reaction of both the drugs with cupric chloride to give light blue colored metal complexes, which are then extracted with dichloromethane and digested with 0.1 M nitric acid. Both the drugs are indirectly estimated via determination of copper content in the formed complexes by AAS. The second method is based on the formation of pink colored complexes of both the drugs with cobaltous chloride. These metal complexes are extracted with dichloromethane and estimated via determination of cobalt content in the formed complexes after digestion with 0.1 M nitric acid by AAS.